X linked spastic paraplegia (SPG2): clinical heterogeneity at a single gene locus. Issue 5 (May 1993) - Bonneau, D; Rozet, J M; Bulteau, C; Berthier, M; Mettey, R; Gil, R; Munnich, A; Le Merrer, M
Abstract : X linked hereditary spastic paraplegia is a rare condition that has been divided into two forms (the pure spastic form and the complicated form) as a function of clinical course and severity. A gene for pure hereditary spastic paraplegia (SPG2) has been mapped to the proximal long arm of the X chromosome (Xq21) by linkage to the DXS17 locus, while a gene for a complicated form of the disease has been mapped to the distal long arm by linkage to the DXS52 locus (Xq28). Here we report on the mapping of a gene for complicated hereditary spastic paraplegia to the Xq21 region by linkage to the probe S9 at the DXS17 locus (Z = 5 at theta = 0.04) in a three generation pedigree. Multipoint linkage analysis supports the distal location of the disease gene with respect to the DXYS1-DXS17 block (cen-DXYS1-DXS3-DXS17-SPG2-tel). The observation of a complicated form of spastic paraplegia mapping to Xq21 raises the difficult issue of variable phenotypic expression, allelic heterogeneity, or even close proximity of two genes for hereditary spastic paraplegia in this region. However, since our study provides clinical evidence for intrafamilial heterogeneity in complicated X linked spastic paraplegia, the present data support the hypothesis of variable clinical expression of a single gene at the SPG2 locus, as previously suggested for SPG1. Finally, we report here what we believe to be the first evidence of clinical expression in heterozygous carriers, a feature that is relevant to genetic counselling in at risk females.